Management of anticoagulation in pregnant women with venous thromboembolism: An international survey of clinical practice. Issue 210 (February 2022) - Simard, C.; Malhamé, I.; Skeith, L.; Carson, M.P.; Rey, E.; Tagalakis, V.; ,
Abstract: Introduction: Venous thromboembolism (VTE) is an important cause of maternal morbidity and mortality. During pregnancy, VTE is treated with low-molecular-weight-heparin (LMWH). Studies assessing the optimal duration and peripartum management of therapeutic anticoagulation are lacking. This survey aimed to assess clinician practices for the management of anticoagulation in pregnant women with acute VTE. Methods: An electronic survey consisting of clinical scenarios addressing anticoagulation management for VTE in pregnancy was created. The target sample was clinicians likely to be involved in the management of pregnant women with acute VTE. The survey completion rate and proportion of individuals selecting a response were determined. Results: 96 respondents completed the survey including general internists (56.3%), hematologists (21.9%), and obstetricians (6.3%). In the management of a VTE in first or second trimester, most respondents preferred therapeutic LMWH until 6 weeks postpartum. In the first and second trimester, 48.0% and 37.5% of respondents, respectively, opted to reduce the dose of anticoagulation after 3 or 6 months. 29.2% of physicians opted for bridging with intravenous heparin around delivery when treating a VTE in the third trimester. 73.0% perceived an increased risk of clinically relevant non-major bleeding associated with the use of therapeutic anticoagulation in the peripartum and postpartum periods. Conclusions: The survey highlights a wide variability of practice in the management of therapeutic anticoagulation in pregnancy. Larger scale studies with relevant clinical outcomes including thrombosis and bleeding risks are needed to inform clinical practice. Highlights: Venous thromboembolism (VTE) causes significant maternal morbidity and mortality. Anticoagulation recommendations for VTE in pregnancy are variable. This survey showed a wide variety of anticoagulation practices for VTE in pregnancy. The acute and peripartum management of therapeutic anticoagulation differed. Larger scale studies are needed to better inform clinical practice.